CD34+/CD38− acute myelogenous leukemia cells aberrantly express CD82 which regulates adhesion and survival of leukemia stem cells1. Issue 9 (30th October 2012) - Nishioka, Chie; Ikezoe, Takayuki; Furihata, Mutsuo; Yang, Jing; Serada, Satoshi; Naka, Tetsuji; Nobumoto, Atsuya; Kataoka, Sayo; Tsuda, Masayuki; Udaka, Keiko; Yokoyama, Akihito
Abstract To identify molecular targets in leukemia stem cells (LSCs), this study compared the protein expression profile of freshly isolated CD34+/CD38− cells with that of CD34+/CD38+ counterparts from individuals with acute myelogenous leukemia (n = 2, AML) using isobaric tags for relative and absolute quantitation (iTRAQ). A total of 98 proteins were overexpressed, while six proteins were underexpressed in CD34+/CD38− AML cells compared with their CD34+/CD38+ counterparts. Proteins overexpressed in CD34+/CD38− AML cells included a number of proteins involved in DNA repair, cell cycle arrest, gland differentiation, antiapoptosis, adhesion, and drug resistance. Aberrant expression of CD82, a family of adhesion molecules, in CD34+/CD38− AML cells was noted in additional clinical samples (n = 12) by flow cytometry. Importantly, down‐regulation of CD82 in CD34+/CD38− AML cells by a short hairpin RNA (shRNA) inhibited adhesion to fibronectin via up‐regulation of matrix metalloproteinases 9 (MMP9) and colony forming ability of these cells as assessed by transwell assay, real‐time RT‐PCR, and colony forming assay, respectively. Moreover, we found that down‐regulation of CD82 in CD34+/CD38− AML cells by an shRNA significantly impaired engraftment of these cells in severely immunocompromised mice. Taken together, aberrant expression of CD82 might play a role in adhesion of LSCs to bone marrow microenvironment and survival of LSCs. CD82 could be an attractive molecular target to eradicate LSCs.